Evaluation of Onco E6 point of care rapid diagnostic test for human papilloma virus in Bahir Dar, Amhara Regional State, Ethiopia - Alemayehu Abate; Abaineh Munshea; Endalkachew Nibret; Belay Bezabih; Bereket Amare; Gizachew Yismaw (PLoS ONE, 2025)
Introduction Cervical cancer is a malignant tumor arising from the cells of the uterine cervix. The oncogenic human papillomavirus (HPV) infection is the main causative agent of cervical cancer. Effective HPV screening program can lead to a significant reduction in the morbidity and mortality associated with this cancer. Objective The aim of the study was to evaluate the diagnostic performance of OncoE6™ cervical test kit for cervical precancer and cancer in Amhara Regional State, northwest Ethiopia. Methods An institute-based cross-sectional study was conducted at Felege Hiwot Compressive Specialized Hospital which is found in Bahir Dar, Amhara Regional state. A total of 297 samples were collected. A sterile, disposable speculum was inserted, without lubricant, and two swabs were taken using the “Tipped Polyester” (Dacron) swab provided with the Onco E6™ kit. Swabs taken were tested for onco E6 proteins testing as per the manufacturer’s protocol and pap smear for cytology test. A punch of biopsy was also taken for histopathological diagnosis. Data for all samples were collected using pre-prepared excel database for onco E6 test, pap cytology and punch histopathology. All the data were coded and entered into Epi-info and transported to SPSS version 26.0 software package for analysis. Results Out of 56 (18.86%) participants who tested positive on the histo-pathological diagnosis, Onco E6 was positive in 32 (57.14%), negative in 24 (42.85%). Of 241 participants who tested negative on the histo-pathological diagnosis, Onco E6 was positive in 5 (2.07%) and negative in 236 (97.9%). OncoE6™ cervical test kit had a sensitivity of 57.14% (95% CI: 43.22%–70.29%) and specificity of 98% (95% CI: 95.23%–99.32%) with positive predictive value of 86.6% (95% CI: 71.36%–95.53%), negative predictive value of 90.76% (95% CI: 86.49%–93.93%), and accuracy of 90.18% (95% CI: 86.21%–93.31%). Conclusion The HPV 16/18 OncoE6™ Cervical test kit test had sub-optimum sensitivity and high specificity for detection of cervical precancer and cancer cases. The sensitivity of the kit could be increased by incorporating other more prevalent genotypes like genotype 52, 58, 31 and 35. The HPV16/18-E6 test could be used either as primary screening tool or in conjunction with other diagnostic methods.